Successful management of difficult airway in an adult patient of Goldenhar syndrome - Sahni, Neeru (Saudi J Anaesth, 2014)
The present case emphasizes on the increasing difficulty in management of patients with Goldenhar syndrome as they age. Fiberoptic intubation using high dose dexmedetomidine along with local anesthetics is a safe technique for securing the airway in a difficult situation, even if the patient dose not cooperates for awake procedure. A16-year-old Goldenhar patient with multiple facial deformities was scheduled for correction of hollowness of right cheek and was successfully managed with high dose dexmedetomidine infusion along with local anesthetics to facilitate fiberoptic intubation with no untoward side-effects.